Investigating the Factors of Consumers’ Purchase Intention Towards Life Insurance in Bangladesh: An Application of the Theory of Reasoned Action - Nomi, Marzia; Sabbir, Md. Mahiuddin (Asian Academy of Management Journal, 2020)
This study aims to examine the factors that influence consumer purchase intention towards life insurance. The study included religiosity, risk aversion motives, saving motives, and financial literacy with classical Theory of Reasoned Action (TRA), therefore extending the model. A convenience sampling method was employed to collect data from 315 respondents working in different public and private institutions in Bangladesh. Collected data were analysed using the structural equation model (SEM). The results revealed that attitude, subjective norms, risk aversion motives, saving motives, and financial literacy have a significant positive impact on consumer purchase intention towards life insurance. Moreover, religiosity was found to have a negative impact on purchase intention. In addition, saving motives was found as a mediator in the relationship between risk aversion motives and purchase intention, as well as between financial literacy and purchase intention. Since attitude and subjective norms were found to have the most effect on purchase intention, the study implicated that marketers should emphasise company image, reputation, and the credibility of the agents, together with the significant others to whom we often turn to before making any financial decision. Finally, the study offered directions for further research after divulging several limitations.